2020
DOI: 10.1590/0102-311x00087320
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection in pregnant women, preterm delivery, birth weight, and vertical transmission: a systematic review and meta-analysis

Abstract: In less than four months, the total of confirmed cases of COVID-19 was 1,684,833 worldwide. Outcomes among the public of pregnant women with COVID-19 are still unclear. We performed a systematic review and meta-analysis to analyze whether COVID-19 in pregnant women is related to premature birth and birth weight, and to summarize the diagnostic results of neonates born to mothers with COVID-19 for investigating the possibility of vertical transmission. Searches were performed in PubMed, Scopus, LILACS, Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 62 publications
5
45
1
19
Order By: Relevance
“…The percentage we observed is roughly consistent with the results previously reported by Zeng et al 47 . Overall, many suspected cases have been reported thus far 11,19,23,26,[48][49][50][51][52][53][54][55][56][57] . Neonates born to infected mothers must be tested and carefully clinically monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage we observed is roughly consistent with the results previously reported by Zeng et al 47 . Overall, many suspected cases have been reported thus far 11,19,23,26,[48][49][50][51][52][53][54][55][56][57] . Neonates born to infected mothers must be tested and carefully clinically monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of preterm birth may be confounded by other factors such as the socioeconomic characteristics of patients, decisions to expedite delivery to optimize maternal condition and psychological stress during pregnancy. (Melo et al 2020) In reports where indication for delivery was not clearly specified, extrapolation of data about the rate of spontaneous versus iatrogenic preterm birth was near-impossible. (Kasraeian et al 2020) Hence, the lack of comparable controls negates attributing these complications and outcomes solely to COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Since December 2019 when the infection was first identified, more than 41,000 MEDLINEindexed papers have been published on COVID-19. Up to 31st July 2020, at least 29 systematic reviews on COVID-19 and pregnancy with varying conclusions have been published (Abdollahpour and Khadivzadeh 2020;Akhtar et al 2020;Ashraf et al 2020;Capobianco et al 2020;Della Gatta et al 2020;Deniz and Tezer 2020;Di Mascio et al 2020;Dubey et al 2020;Elshafeey et al 2020;Hessami et al 2020;Juan et al 2020;Kasraeian et al 2020;Kotlyar et al 2020;Lopes de Sousa et al 2020;Matar et al 2020;Melo and Araújo 2020;Muhidin et al 2020;Segars et al 2020;Silva et al 2020;Smith et al 2020;Thomas et al 2020a, b;Trippella et al 2020;Trocado et al 2020;Turan et al 2020;Walker et al 2020;Yang et al 2020;Yoon et al 2020;Zaigham and Andersson 2020). Factors which are likely to cause bias and thus, inaccuracy in subsequent analysis in systematic reviews were then identified and compiled.…”
Section: Methodsmentioning
confidence: 99%
“…165,166 A systematic review of 38 cohort studies found an infection rate of 3.25% neonates from COVID-19-infected pregnant women. 167 In comparison, there have been many reports of COVID-19 patients presenting with neurological abnormalities. ACE2 is primarily expressed in neurons and glial cells of the brain.…”
Section: Pathology In Renal Hepatic Reproductive and Neural Tissuesmentioning
confidence: 99%